Projetar para o presente e futuro. Os conceitos de adaptabilidade e flexibilidade na habitação plurifamiliar - Margarida Maria Botelho Ribeiro (2012)
The reality of the diversified and constantly changing society we live in, confronted with the housing subject-matter, is the motto that leads to the development of this paper. This inconsistency is a growing contemporary condition, leading to a bigger need of adequacy of its related processes, namely in the architectural field, since their instruments "seem" not be sufficient to respond to the complexity of the emerging situation. In this context, this research focuses on finding solutions to counter the static and somehow homogenized aspect of urban housing units, aiming to its better adaptation to the different requirements that manifest in new ways of inhabiting. We aspire, for all matters, a residential architecture which is evolutionary, innovative and suitable for transformation. For that matter, various proposals are generated, grounded in the concepts of adaptability and flexibility which intend to provide housing with the possibility of potential changes that depend on what is temporary: households, needs and desires. The main purpose is to identify and explore the whole process that seeks a set of issues and operating modes of action in order to root relevant ideas to the architectural field, around utilities, programs and the concepts of domestic spaces. Therefore, on the hypothesis of proposing housing for the present and future, a number of strategies were taken into account that aren't influenced by time, i.e. they solve the present but also design the future.